2020
DOI: 10.1074/jbc.ra120.012590
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6–mediated epigenetic control of the VEGFR2 gene induces disorganized angiogenesis in human breast tumors

Abstract: Disorganized vessels in the tumor vasculature lead to impaired perfusion, resulting in reduced accessibility to immune cells and chemotherapeutic drugs. In the breast tumor–stroma interplay, paracrine factors such as interleukin-6 (IL-6) often facilitate disordered angiogenesis. We show here that epigenetic mechanisms regulate the cross-talk between IL-6 and vascular endothelial growth factor receptor 2 (VEGFR2) signaling pathways in myoepithelial (CD10+) and endothelial (CD31+, CD105+, CD146+, and CD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Statistical analysis was performed by one-way ANOVA followed by a post hoc Tukey's multiple-comparison test; *p < 0.05; **p < 0.01; for each ratio, no statistical significance was found between conditions with and without VEGF supplementation at each cell ratio. cytokine secreted by tumor cells and fibroblasts, involved in angiogenesis (Nagasaki et al, 2014;Hegde et al, 2020). IL-6 appeared to be secreted by tumor cells and by fibroblasts and consumed by ECs (Supplementary Figure 8); although further studies will be required to conclude on the role of IL-6, its concentration was not correlated with EC maintenance.…”
Section: Fibroblasts Are Required To Maintain the Ec Populationmentioning
confidence: 99%
“…Statistical analysis was performed by one-way ANOVA followed by a post hoc Tukey's multiple-comparison test; *p < 0.05; **p < 0.01; for each ratio, no statistical significance was found between conditions with and without VEGF supplementation at each cell ratio. cytokine secreted by tumor cells and fibroblasts, involved in angiogenesis (Nagasaki et al, 2014;Hegde et al, 2020). IL-6 appeared to be secreted by tumor cells and by fibroblasts and consumed by ECs (Supplementary Figure 8); although further studies will be required to conclude on the role of IL-6, its concentration was not correlated with EC maintenance.…”
Section: Fibroblasts Are Required To Maintain the Ec Populationmentioning
confidence: 99%
“…IL-6 in turn, can epigenetically regulate other molecular factors. Its inhibition of methyltransferases DNMT1 [ 222 ] and DNMT3B [ 223 ] can possibly impact expression and activity of multiple genes. Not only a direct but even some indirect epigenetic regulation of IL-6 has been suggested.…”
Section: Epigenetic Regulation Of Inflammationmentioning
confidence: 99%
“…IL-6 via IL-6R/STAT3 pathway regulates DNMT1 expression in tumor cells (Huang et al 2016 ). Our recent studies in clinically characterized human breast tumor tissues, we demonstrated IL-6 induced proteasomal degradation of DNMT1 which led to promoter DNA hypomethylation of VEGFR2 promoter and subsequently to disorganized sprout formation in endothelial cells isolated from malignant part of breast tissue (Hegde et al 2020 ).…”
Section: Influence Of Cytokines and Growth Factors In Regulating Dnmtmentioning
confidence: 99%